Elixir of love or venom of violence: When does a drinking event result in couple intimacy or couple conflict?. (January 2023) - Derrick, Jaye L.; Testa, Maria; Wang, Weijun; Leonard, Kenneth E.
Highlights: Alcohol use can lead to either couple intimacy or couple conflict. Some people are more likely to experience intimacy or conflict after drinking. Event characteristics (e.g., quantity) also predict intimacy and conflict. Consistent with alcohol myopia, salient relationship cues also predict outcomes. Abstract: The short-term consequences of drinking events may be positive or negative. Most studies have considered only one outcome, but people may experience different alcohol outcomes on different occasions, depending on the circumstances. The present study sought to identify predictors of drinking events that resulted in couple intimacy, conflict, or neither outcome using existing data from a 30-day ecological momentary assessment (EMA) study. Participants were a community sample of partnered, moderately drinking adults with a recent history of verbal or physical partner aggression ( N  = 249 couples). They provided reports of drinking events, intimacy and conflict events, and ratings of relationship harmony and discord in three randomly signaled reports each day. Mixed-effects multinomial analyses were used to compare predictors of drinking events that, within three hours, resulted in intimacy, conflict, or neither outcome. Consistent with previous research, characteristics of the drinker (individual tendencies to experience intimacy or conflict) and characteristics of the drinking event (alcohol quantity, drinking companions) both predicted drinking outcomes. Moreover, the pre-drinking relationship context predicted post-drinking relationship outcomes, consistent with the idea that alcohol focuses attention on salient contextual cues. Specifically, greater pre-drinking relationship harmony predicted greater likelihood of experiencing intimacy after drinking, whereas greater pre-drinking relationship discord predicted greater likelihood of experiencing conflict after drinking. In summary, characteristics of the drinker, the drinking event, and the pre-drinking relationship context contribute to the likelihood that a given drinking event will have short-term positive or negative relationship outcomes.